Easy access to a carbohydrate-based template for stimuli-responsive surfactants - Holmstrøm, Thomas; Raydan, Daniel; Pedersen, Christian Marcus (Beilstein Journal of Organic Chemistry, 2020)
In this paper we describe the synthesis of a new carbohydrate-based building block functionalized with azido or amino groups on the 2 and 4 positions. The building block can be synthesized in anomerically pure form in only five scalable steps starting from commercially available levoglucosan. It was shown that the building block could undergo alkylations under strongly basic conditions. The building block with azido groups could furthermore take part in CuAAC reactions, generating derivatives with ester or carboxylic acid functionalities. In addition, the anomeric mixture of the building block was used for the synthesis of a molecule that could act as an emulsifier only in the presence of Zn2+ ions.
Keywords: carbohydrates; emulsifiers; stimuli-responsive; surfactants; synthesis